The role of Voivodeship conservator of monuments in protection and management of historic monuments on the example of Warsaw and Mazovia - Lewicki, Jakub (Protection of Cultural Heritage, 2019)
The text discusses the role of the Voivodeship Conservator in the protection and management of a Historic Monument on the example of activities in Warsaw and Mazovia region. The most important role of a Voivodeship Conservator of Monuments is to carry out supervision over objects of heritage located within the area of a Historic Monument. By doing so, the VCM can promote high standards of conservation work and create examples of protection and conservation projects in an area, as well as conduct promotional activities. Presented here are all objects registered as Historic Monuments in the Mazovia region, as well as the submitted applications and the listed monuments that deserve to be bestowed the rank of the Historic Monument. Despite the restrictions imposed by law, the VCM may actively work for the protection of Historic Monuments and be the executor of the national heritage policy. It can also very efficiently combine sustainable development considerations of the areas of Historic Monuments with the requirements of conservation, development, as well as protection and adaptation to the changing needs of life.